Use of Acid Ceramidase and Sphingosine Kinase Inhibitors as Antiviral Compounds Against Measles Virus Infection of Lymphocytes in vitro - Grafen, Anika; Schumacher, Fabian; Chithelen, Janice; Kleuser, Burkhard; Beyersdorf, Niklas; Schneider-Schaulies, Jürgen (Frontiers in Cell and Developmental Biology, 2019)
As structural membrane components and signaling effector molecules sphingolipids influence a plethora of host cell functions, and by doing so also the replication of viruses. Investigating the effects of various inhibitors of sphingolipid metabolism in primary human peripheral blood lymphocytes (PBL) and the human B cell line BJAB we found that not only the sphingosine kinase (SphK) inhibitor SKI-II, but also the acid ceramidase inhibitor ceranib-2 efficiently inhibited measles virus (MV) replication. Virus uptake into the target cells was not grossly altered by the two inhibitors, while titers of newly synthesized MV were reduced by approximately 1 log (90%) in PBL and 70-80% in BJAB cells. Lipidomic analyses revealed that in PBL SKI-II led to increased ceramide levels, whereas in BJAB cells ceranib-2 increased ceramides. SKI-II treatment decreased sphingosine-1-phosphate (S1P) levels in PBL and BJAB cells. Furthermore, we found that MV infection of lymphocytes induce a transient (0.5 to 6 h) increase in S1P, which was prevented by SKI-II. Investigating the effect of the inhibitors on the metabolic (mTORC1) activity we found that ceranib-2 reduced the phosphorylation of p70 S6K in PBL, and that both inhibitors, ceranib-2 and SKI-II, reduced the phosphorylation of p70 S6K in BJAB cells. As mTORC1 activity is required for efficient MV replication, this effect of the inhibitors is one possible antiviral mechanism. In addition, reduced intracellular S1P levels affect a number of signaling pathways and functions including Hsp90 activity, which was reported to be required for MV replication. Accordingly, we found that pharmacological inhibition of Hsp90 with the inhibitor 17-AAG strongly impaired MV replication in primary PBL. Thus, our data suggest that treatment of lymphocytes with both, acid ceramidase and sphingosine kinase inhibitors impair MV replication by affecting a number of cellular activities including mTORC1 and Hsp90, which alter the metabolic state of the cells causing a hostile environment for the virus.